CATATAN KESIAPAN INDONESIA UNTUK SKEMA PENGURANGAN EMISI DARI DEFORESTASI DAN DEGRADASI HUTAN - Tigor Butarbutar (Jurnal Analisis Kebijakan Kehutanan, 2016)
The scope of Readiness Package (R-P) for Reducing Emission from Deforestation and Forest Degradation (REDD+) nationwide and covers all the main activities that REDD+ strategy, implementation framework, reference emission level, monitoring system and safeguards. The method based on the Forest Carbon Partnership Facility (FCPF) guideline for R-P assessment by answers to 41 diagnostic questions for 35 readiness criteria of 5 (five) components/ 9 (nine) sub-components.Based on this study suggested that for the 1st component of REDD+strategy, required strengthening the institutions which will implement REDD+. For the 2st nd component of implementation framework, it is important to develop a procedure and standard for identification and mitigationdriver deforestation and degradation (DD). For the 3rd component, the reference emissions level (REL) need to be improved by validation to rd sub-national/local data (from tier 1 to tier 3 and up to five carbon pools). For the 4 component ofMeasurement, Reproting and th Verification (MRV) system such as forest monitoring need to be strengthened the capacity of human resources, particularly people who want to join the REDD+ scheme. Finally, for the 5th component, all the guideline related to safeguards need to be harmonized and synergized.